Synthesis of Control System with Model To Be Adjusted - O. F. Opeyko (Наука и техника)
The paper considers the method of synthesis of a system with a dual model which is to be adjusted. The method is based on division of motions. It is supposed that the adaptation process is passing quicker than the process of the main system circuit. Parameters of the object may be considered as permanent ones during the transient process. The result of system modeling is given in the paper.